Abstraction of tactile properties by individuals with autism and Down syndrome using a picture‐based communication system. Issue 2 (7th December 2018) - Belisle, Jordan; Stanley, Caleb R.; Alholail, Amani M.; Galliford, Megan E.; Dixon, Mark R.
Abstract : The present study evaluated the efficacy of a set of procedures for bringing tact extensions of abstract tactile properties under stimulus control. Two participants with disabilities who communicated via a picture‐based communication system received reinforcement for tacts of tactile properties of four wet/dry and four hard/soft stimuli. Test trials were conducted to evaluate the extent to which the participants' correct responding generalized to novel stimuli with the same tactile properties. The results suggest that the procedures were effective in bringing tact extensions of abstract tactile properties under stimulus control. Both participants' correct responding generalized to a set of novel stimuli. Mastery level responding to training and test targets maintained for 2 weeks following training. The results provide further evidence supporting the use of DTT to teach stimulus abstraction to nonvocal verbal individuals who use augmentative forms of communication.